Unveiling Global Research Trends and Collaboration Patterns in Alzheimer’s Disease: A Bibliometric Perspective - Prasetyaning Amukti, Danang; Pratami, Ria Indah; Estiningsih, Daru; Saiful Bachri, Moch; Muhammad Ma’ruf; Djaka Purwanto, Barkah; Sukma Ananda, RA Dewinta; Suminingtyas, Ifa Aris; Akbar, Imam (Universitas Ahmad Dahlan, 2026)
Alzheimer's disease is one of the most common forms of dementia and poses a major challenge to global health, especially as the aging population increases. With the high research interest in this topic, a scientific mapping is needed to identify trends, major contributors, and current research focuses in the field of Alzheimer's. This study uses a bibliometric approach with a Scopus database published in the period 2023 to 2025, then the data is analyzed using bibliometrix software. The results show an annual publication growth rate of 19.67% with an average of citations per document of 3,524. The most productive journals are alzheimer's and dementia (1,093 documents), followed by Journal of Alzheimer's Disease (817 documents). The most active authors are Wang Y (493 documents), Zhang Y (437), and Li Y (410). The most affiliations come from University of California And Harvard Medical School, while the countries with the largest contributions are the United States, China, and India. Alzheimer's research shows rapid development in terms of quantity and international collaboration. The United States and China are the main centers of scientific contribution, both in terms of the number of publications and citations. These results are important as a basis for making research policies, cross-country collaborations, and determining the direction of future research in efforts to overcome alzheimer's disease.